Temuan Klinis Akut Pseudomembran Candidiasis Pada Pasien Tuberkulosis (TB): Laporan Kasus - Maulina Triani; Aditya Priagung Prakosa; Suci Idia Artika; Tri Utomo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Tuberculosis (TB) caused by strains of Mycobacterium tuberculosis complex (M. tuberculosis), is a pulmonary infection that is spread by airborne droplet transmission. Highest incidences occurred in India. Indonesia soared on 2th place worldwide with 420.994 cases of tuberculosis in 2017. Most of TB patients do not maintain oral hygine and are smokers which can cause several oral manifestations such as oral candidiasis. The purpose of this case report is to describe the oral manifestations that occur in tuberculosis patients. A 39-year-old male patient complained of white plaques on tongue and sore throat since 2 weeks ago. The patient has a history of TB. The patient is being treated at Prof. Dr. Margono Soekardjo Hospital. Treatment plans that can be given is pharmacological therapy. Topical antifungal drug therapy is nystatin oral suspension. Non-pharmacological therapy in the form of communication, information, and education provided to patients in order to avoid some of the predisposing factors for candidiasis and the need for collaboration with pulmonary specialists who are dealing with systemic diseases. The key of success treatments for patient are management of oral candidiasis include administration of antifungal agents to suppress fungal, identification and elimination of predisposing factors and good communication, information and education.